The effects of seeding density on production traits and stress biomarkers of the Greenshell™ mussel, Perna canaliculus : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Conservation Biology at Massey University, Albany, New Zealand - Reyden, Carrie (Massey University, 2021)
The Greenshell™ mussel, Perna canaliculus, is New Zealand’s most important aquaculture species and holds great economic significance. Losses of juvenile mussels (spat) are common and can severely reduce the potential yield of P. canaliculus, however the exact drivers of these losses are unknown. Environmental variation inevitably contributes to mussel performance, however, environmental factors are difficult to control in a water-based aquaculture system, such as P. canaliculus farms. Therefore, it is important to understand how controllable factors, such as commercial procedures, impact mussel performance so modifications can be implemented. In this study, I assessed the impacts of seeding density (257, 515, and 1030 mussels 10cm⁻¹ of culture rope) on P. canaliculus performance on commercial mussel farms in the Marlborough Sounds. In a spatially replicated field experiment during the austral summer in the initial stages of culture when spat loss is common, I explored the effects of seeding density on production traits: P. canaliculus abundance and size, as well as accumulation of biofouling on culture ropes and stress biomarkers in P. canaliculus by assessing a stress effect: total antioxidant capacity (TAC), and stress responses: oxidative stress, and viability (valve closure during freshwater immersion). At the end of my experiment, P. canaliculus abundance remained greatest at the highest seeding density, however losses were also greatest at the highest seeding density, and P. canaliculus growth was greater at shallow depths. The abundance of a problematic biofouling species, Mytilus galloprovincialis, was greatest at low seeding densities and shallow depths, and varied between sites. Mytilus galloprovincialis were also larger at shallow depths. Shallower depths and Site 2 attracted a greater biomass of non-mussel biofouling. Although, TAC in P. canaliculus varied among seeding density treatments, the impacts of seeding density were inconsistent among depths, sites, and time. Nonetheless, while mussel viability remained high in all treatments oxidative stress appeared greater near the end of summer. Ameliorating challenging conditions increases the capacity of mussels to respond to additional stressors, including uncontrollable environmental factors and future climate change. However, my results indicate seeding density influences whole-organism and stress biomarkers differently and underlies trade-offs between favourable mussel production traits for farmers to consider.
Keywords: 410406 Natural resource management